Erfaring og sprog - Løwenstein, Casper (Studier i Pædagogisk Filosofi, 2014)
The article examines the relation between experience and language. By drawing on the work of Heidegger and others, its objective is to defend the idea that experience is protolinguistic: language begins and works within experience itself. Through a study of different traits in experience – e.g. movement, negativity, trying, being marked, changing –, the investigation challenges scientific, metaphysical, and everyday conceptions of experience as well as the idea of language as system and communication, and it suggests a widening of the concept of experience in order to help understanding how experience, thought, language, and use of language are intertwined.